Classroom Management Strategies and Their Impact on the Behavior and Academic Performance of Intermediate Pupils - De Rosas, Allaiza Nicole (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the impact of classroom management strategies on the behavior and academic performance of intermediate pupils at Tomas Claudio Colleges during the School Year 2025–2026. The study employed a descriptive survey research design complemented by documentary analysis. The respondents consisted of 247 intermediate pupils selected through total population sampling. A researcher-made questionnaire was utilized to assess the perceived impact of classroom management strategies on pupils' behavior in terms of emotional regulation, self-efficacy, and social skills, while documentary analysis of pupils' average grades was conducted to determine their academic performance. Descriptive and inferential statistical tools were used in analyzing the data. Findings revealed that most respondents were female, first- or second-born, belonged to families with two children, had a monthly family income of ₱50,000 and above, had parents who were predominantly college graduates, and whose parents were mostly government employees. Classroom management strategies were perceived to have a high impact on pupils' emotional regulation, self-efficacy, and social skills. Significant differences in these perceived impacts were found when respondents were grouped according to monthly family income, parents' educational attainment, and parents' occupation, while no significant differences were observed based on sex, sibling position, and family size. The respondents obtained a Very Satisfactory level of academic performance. Furthermore, a significant positive relationship was established between classroom management strategies and pupils' behavior and academic performance. The study concluded that effective classroom management strategies contribute to the development of positive behavioral outcomes and improved academic achievement among intermediate pupils. It is recommended that school administrators and teachers strengthen evidence-based classroom management practices through continuous professional development, foster home-school collaboration, integrate activities that enhance emotional regulation, self-efficacy, and social skills, implement the proposed action plan, and conduct further studies incorporating additional variables to broaden the findings.
Keywords: Classroom Management Strategies, Behavior, Academic Performance, Emotional Regulation, Self-Efficacy, Social Skills, Intermediate Pupils